Perencanaan Struktur Atas Jembatan Komposit Sungai Nipah Desa Darul Aman Kecamatan Rupat - Indriyani Puluhulawa; Nur Aspaliza; Armada Armada (P3M Politeknik Negeri Banjarmasin, 2018)
The Darul Aman Village Bridge was originally a wooden bridge connecting community settlements with harbor and plantation areas. Yhe current condition of the bridge is not worth crossing because the wooden structure on the bridge has severe weathering, so it is very risky if forced to pass through the vehicle continuously and will cause further damage.for this purpose a nwe bridge is planned using a composite structure between steel girder and concrete slab. This plan refers to SNI T-02-2005 for loading bridge and SNI T-03-2005 fot steel structure planning. The planned plan includes bridge slab, girders, diaphragms and bridge elastomeric placement. From the result of the planning, the steel girder profile is using WF 800.300.14.26 , with a gap between 1,125 m. The steel angles profile diaphragm 70.70.7 mm using with a gap 4 m diaphragm, the elastomeric placement diameter is 175.175.12 mm